Solvent‐Assisted Low‐Temperature Crystallization of SnO2 Electron‐Transfer Layer for High‐Efficiency Planar Perovskite Solar Cells. (23rd May 2019) - Chen, Cong; Jiang, Yue; Guo, Jiali; Wu, Xiayan; Zhang, Wenhui; Wu, Sujuan; Gao, Xingsen; Hu, Xiaowen; Wang, Qianming; Zhou, Guofu; Chen, Yiwang; Liu, Jun‐Ming; et al.
Abstract: A high‐quality polycrystalline SnO2 electron‐transfer layer is synthesized through an in situ, low‐temperature, and unique butanol–water solvent‐assisted process. By choosing a mixture of butanol and water as a solvent, the crystallinity is enhanced and the crystallization temperature is lowered to 130 °C, making the process fully compatible with flexible plastic substrates. The best solar cells fabricated using these layers achieve an efficiency of 20.52% (average 19.02%) which is among the best in the class of planar n–i–p‐type perovskite (MAPbI3 ) solar cells. The strongly reduced crystallization temperature of the materials allows their use on a flexible substrate, with a resulting device efficiency of 18%. Abstract : In situ synthesis of polycrystalline SnO2 electron‐transfer layers (ETLs) at temperatures as low as 130 °C is developed. The best efficiency of devices fabricated using these ETLs is up to 20.52% for those based on glass and 18% for those based on a flexible substrate, among the best for planar n–i–p‐type perovskite (MAPbI3 ) solar cells.